Openness to experience predicts dopamine effects on divergent thinking. (2019) - Käckenmester, Wiebke; Bott, Antonia; Wacker, Jan
Abstract: Individual differences in trait levels of openness to experience and creativity have been theoretically linked to dopamine function. However, empirical evidence for this assumption is scarce, especially for causal connections. The present study aims to directly assess the influence of dopamine activity on the established association between openness to experience and divergent thinking (i.e., an index of creativity). We hypothesized that manipulating dopamine activity alters the relationship between self-reported openness to experience and ideational fluency and flexibility. In a placebo-controlled between-subjects design, 193 healthy male volunteers completed four divergent thinking tasks after they received either the dopamine-receptor blocker sulpiride (200 mg) or a placebo. The data revealed an interaction such that openness to experience was more positively associated with divergent thinking in the dopamine blocker group ( r = 0.304) than in the placebo group ( r = −0.002). Specifically, highly open individuals in the dopamine blocker group reached the highest divergent thinking scores. Thus, sulpiride administration selectively affected divergent thinking as a function of trait levels of openness to experience. Although somewhat limited by the unexpected absence of the association between openness to experience and divergent thinking in the placebo group, the present study provides novel evidence for an association between dopamine activity and both openness to experience and divergent thinking.